Determinants of Open Unemployment in Indonesia: The Role of Average Length of Schooling, Minimum Wage, and Economic Growth - M. Deni Damara; Kautsar Fatin Dharmawan Nasution; Bunga Ananda; Cindy Eleonora Sitohang; Era Widia Br. Sinaga; Elisa Clara Saragih; Melani Manginar Sirait; Relli Anisma Hutabalian; Noni Rozaini (Jurnal Ekonomi Balance, 2026)
Open unemployment remains one of the most persistent socioeconomic challenges in Indonesia, despite continuous improvements in macroeconomic performance and labor market policies. This study investigates the effects of Average Length of Schooling (ALS), Minimum Wage (MW), and Economic Growth (EG) on the Open Unemployment Rate (OUR) in Indonesia over the 2015–2024 period. A descriptive-verificative quantitative approach was employed using annual secondary data obtained from Statistics Indonesia (BPS). The data were analyzed using multiple linear regression with EViews software. Prior to hypothesis testing, the model was evaluated through classical assumption tests, while the significance of the relationships was assessed using the t-test, F-test, and coefficient of determination (R²). The empirical findings indicate that, individually, Average Length of Schooling and Minimum Wage do not have a statistically significant effect on the Open Unemployment Rate. In contrast, Economic Growth has a significant negative effect, indicating that higher economic growth contributes to lower unemployment levels by expanding employment opportunities and stimulating productive economic activities. Simultaneously, the three independent variables significantly influence the Open Unemployment Rate, with an R² value of 0.82, suggesting that the model explains approximately 82% of the variation in unemployment during the study period. These findings emphasize that sustainable economic growth remains the primary driver of employment creation, whereas education and wage policies require stronger alignment with labor market demands. The study provides empirical evidence for policymakers to formulate integrated, inclusive, and sustainable employment strategies that enhance workforce competitiveness and support long-term economic development.